Exploring rural palliative care patients’ experiences of accessing psychosocial support through telehealth: A longitudinal approach - Rachel J. Rahman; Joseph R. Keenan; Joanne Hudson (Qualitative Research in Medicine & Healthcare)
In this research, we explore the experiences of rural palliative care patients receiving psychosocial support through telehealth. A longitudinal approach considered how experiences vary over time. Three patients with a terminal cancer diagnosis were given a laptop to access psychosocial support via telehealth over three months. Semi-structured interviews were conducted at monthly intervals. Interpretative phenomenological analysis identified four themes: Deepening understanding through unburdened and continuous connections; the ever-present paradox of visible and invisible telehealth; insight into the holistic self: from barrier to facilitator; and, the immediate change from unnecessary distraction to mindful engagement. Findings challenge previous conclusions regarding the inability of telehealth to support meaningful relationships, and instead provide novel insights to explain why enabling rural palliative care patients to access support from home is supportive for their wellbeing and the quality of healthcare relationships. Our conclusions question whether the indirect benefits of telehealth could also offer a valuable way of accessing health services beyond a palliative care setting.